THE EFFECT OF PARENTS OF KNOWLEDGE AND MOTIVATION ON POSYANDU SERVICES IN ILOPONU VILLAGETIBAWA DISTRICT GORONTALO REGENCY - muhtar rahim; lisda van gobel; laksmyn kadir (LP2M Universitas Bina Mandiri Gorontalo, 2023)
The aims of this study were (1) to determine the effect of parental knowledge on posyandu services in Iloponu Village, Tibawa District, Gorontalo Regency; 2) To determine the effect of the motivation of parents of toddlers on posyandu services in Iloponu Village, Tibawa District, Gorontalo Regency; 3) To determine simultaneously the influence of knowledge and motivation of parents of toddlers on posyandu services in Iloponu Village, Tibawa District, Gorontalo Regency. This study uses a quantitative approach with a quasi-experimental method, primary data obtained through a survey of 73 parents of children under five with data collection techniques. Data analysis using computer program Microsoft excel and statistical program. Data analysis includes univariate analysis by looking for frequency distribution, while bivariate analysis uses independent sample t test with sig (2-tailed) < 0.05 The results of this study indicate that: 1) There is a positive and significant influence between the knowledge of parents of toddlers on posyandu services in Iloponu Village, Tibawa District, Gorontalo Regency in 2021, based on the results of statistical tests using quasi-experimental tests, H0 is rejected and Ha is accepted because it is sig. = 0.000 <0.05, which means that there is an influence of the knowledge of parents of children under five on posyandu services; 2) There is a positive and significant influence between the motivation of parents of toddlers on posyandu services in Iloponu Village, Tibawa District, Gorontalo Regency in 2021, based on the results of statistical tests using quasi-experiments, H0 is rejected and Ha is accepted because sig = 0.000 < 0.05 which means that there is an influence of the motivation of parents of toddlers on posyandu services; 3) There is a positive and significant influence between the knowledge and motivation of parents of toddlers on posyandu services in Iloponu Village, Tibawa District, Gorontalo Regency in 2021, based on the results of statistical tests using an independent sample t test, H0 is rejected and Ha is accepted because sig = 0.000 <0.05, which means that there is an influence of knowledge and motivation of parents of toddlers on posyandu services.